PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS GOOGLE CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB DI SMAIT ALBIRUNI MANDIRI MAKASSAR - Ismail, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2022)
This research is a Pre Experimental Design research and uses the One Group Design research design. The population in this study were all three classes of SMAIT Albiruni Makassar students registered in 2019/2020 with a total of 49 respondents. The instrument used was a test, analyzed using descriptive hypothesis submission techniques and associative hypothesis testing in collecting processed data. The results of data processing and analysis concluded that: 1) The results of learning Arabic for SMAIT Albiruni Mandiri Makassar students without using Google Classroom, 45% of students are in the low category, 12% are in the medium category, 33% are in the high category and 10% is in the very high category. 2) Arabic Learning Outcomes of Students of SMAIT Albiruni Mandiri Makassar using Google Classroom, 14% are in the low category, 29% are in the medium category, 43% are in the high category and 14% are in the very high category. 3) Based on the results of the analysis, it is proven that there are differences in Arabic learning outcomes by using google classroom based learning media.Arabic Learing Media, google classroom, learning outcomes